On introduction of security measures as criminal sanctions - Drakić Dragiša (Anali Pravnog Fakulteta u Beogradu)
In this article the author deals with an analysis of ideas that served as the basis on which the doctrine of security measures as modern criminal sanctions, later developed. The presentation begins with citing and interpreting Protagoras's and Plato's positions by which they tried to justify state sanctions. In search of ideas that contributed to the emergence of security measures as modern criminal sanctions, the author examines certain medieval sources of law, followed by analysis of provisions of the French Law that introduced the so called eliminating security measures. The central part of the article lists and interprets positions of classical, positivistic, and sociological school of criminal law that relate to the principle aim of study of this article. The author puts great emphasis on the teachings of the school of thought last mentioned above. At the turn of the XX Century, under the influence of this school of thought majority of European criminal legislations introduced security measures. In the end, the author concludes that security measures were, regardless of their destiny in future development in criminal law of European countries, envisaged, at the time when they were introduced in the European criminal legislation at the beginning of the XX Century, as exceptionally humane criminal sanctions that were the result of an attempt to make the society better and more humane through a more humane approach towards criminal offenders.